Striving for Diversity, Accessibility and Quality: Evaluating SiSAL Journal - Jo Mynard (Studies in Self-Access Learning Journal, 2014)
After establishing a journal, it is important to evaluate its progress to ensure that the principles that underpin its existence continue to be a priority. In this article, the author reports on measures that were used to evaluate Studies in Self-Access Learning (SiSAL) Journal. The research was designed to investigate the three principles that the journal values: diversity, accessibility and quality. The results identified some successful factors such as accessibility and favourable perceptions of SiSAL Journal’s quality. However, the results also identified areas that could be improved to further increase diversity and to encourage submissions from more authors based in different locations.